Winter feeding effects on female reindeer (Rangifer tarandus tarandus) gut microbiota and to short chain fatty acid production - Mönttinen, Miitri (2022)
Gut microbiota (the community of microbes) metabolises otherwise undigestible components of the diet, most of all those found in plant and lichen cell walls. This process forms short-chain fatty acids (SCFA) which are used as an energy source by the host. Dietary changes such as those occurring naturally between seasons will shape the gut microbiota composition which affects the type and quantity of SCFAs. In this study, I quantify the differences in female reindeer (Rangifer tarandus tarandus) (n=60) faecal microbiota and SCFAs under experimental conditions between two commonly used winter husbandry methods in (1) pens (fully supplemented) and in (2) pastures (mostly forage). Longitudinal samples for 16S rRNA V4-region amplicon sequencing were collected between 26.11.2019 and 23.03.2020. During the experiment, the faecal microbiota of reindeers in pastures had a significant decrease in alpha diversities and a major increase of Bifidobacteriales (from <1% to 22% of the whole community abundance). Whereas pen reindeer had a consistent microbiota throughout the experiment. These results indicate that in pen reindeer the naturally occurring change is effectively suppressed by the used husbandry method. Whereas the increase of Bifidobacteriales might be beneficial to the offspring of pasture reindeer via vertical transmission as it is connected to milk metabolism.